Structural and functional characterization of a ubiquitin variant engineered for tight and specific binding to an alpha‐helical ubiquitin interacting motif. (24th March 2017) - Manczyk, Noah; Yates, Bradley P.; Veggiani, Gianluca; Ernst, Andreas; Sicheri, Frank; Sidhu, Sachdev S.
Abstract: Ubiquitin interacting motifs (UIMs) are short α‐helices found in a number of eukaryotic proteins. UIMs interact weakly but specifically with ubiquitin conjugated to other proteins, and in so doing, mediate specific cellular signals. Here we used phage display to generate ubiquitin variants (UbVs) targeting the N‐terminal UIM of the yeast Vps27 protein. Selections yielded UbV.v27.1, which recognized the cognate UIM with high specificity relative to other yeast UIMs and bound with an affinity more than two orders of magnitude higher than that of ubiquitin. Structural and mutational studies of the UbV.v27.1‐UIM complex revealed the molecular details for the enhanced affinity and specificity of UbV.v27.1, and underscored the importance of changes at the binding interface as well as at positions that do not contact the UIM. Our study highlights the power of the phage display approach for selecting UbVs with unprecedented affinity and high selectivity for particular α‐helical UIM domains within proteomes, and it establishes a general approach for the development of inhibitors targeting interactions of this type. Abstract : Interactive Figure 2 | PDB Code(s):5UCL